One-time fertilization at first flowering improves lint yield and dry matter partitioning in late planted short-season cotton - Hong-hai LUO; Qiang WANG; Jie-kun ZHANG; Lei-shan WANG; Ya-bing LI; Guo-zheng YANG (Journal of Integrative Agriculture, 2020)
Cotton producers have substantially reduced their inputs (labor, nutrients, and management) mainly by adopting a short-season cropping management that is characterized by late sowing, high density, and reduced fertilization with one-time application at the first bloom stage without lint yield reduction. However, it has been hypothesized that one-time fertilization at an earlier growth stage could be a more effective and economic management practice. A two-year field experiment was conducted by applying five fertilizer one-time fertilization at 0 (FT1), 5 (FT2), 10 (FT3), 15 (FT4), and 20 (FT5) days after the first flower appeared in the field and one three-split fertilizer application taken as the conventional control (FT6), making six treatments altogether. Cotton growth period, biomass accumulation, yield, and its formation were quantified. The results showed that the one-time fertilization did not affect the cotton growth progress as compared to FT6, however, the total crop cycles for FT3–FT5 were 3 days shorter. FT1 produced the highest cotton lint yield (1 396 kg ha−1), which was similar to the FT6 but higher than the other treatments, and could be attributed to more bolls per unit area and higher lint percentage. Cotton yield was positively correlated with cotton plant biomass accumulated. FT1 had both the highest average (VT) (193.7 kg ha−1 d−1) and the highest maximum (VM) (220.9 kg ha−1 d−1) rates during the fast biomass accumulation period. These results suggest that one-time fertilizer application at the first flower stage might be an adjustment that is more effective than at first bloom, and allowed for easier decision making for application date due to non counting of plants with flowers is needed.